Comparison of the Gross Target Volumes Based on Diagnostic PET/CT for Primary Esophageal Cancer - Shi, Jingzhen; Li, Jianbin; Li, Fengxiang; Zhang, Yingjie; Guo, Yanluan; Wang, Wei; Wang, Jinzhi (Frontiers in Oncology, 2021)
Background Clinically, many esophageal cancer patients who were prepared for radiation therapy already had diagnostic PET/CT image, but it has not been clear whether we can directly refer to the diagnostic PET/CT to delineate the gross target volume (GTV) of the primary tumor for thoracic esophageal cancer (EC). Methods Seventy-two patients diagnosed with thoracic EC and undertaken PET/CT scan for diagnosis and 3DCT scan for simulation. GTV3D was contoured on 3DCT image without referencing PET/CT image. GTVPET-ref was contoured on 3DCT image referencing PET/CT image. GTVPET-reg was contoured on the deformed registration image derived from 3DCT and PET/CT. Differences in the position, volume, length, conformity index (CI), and degree of inclusion (DI) among the target volumes were determined. Results The centroid distance in the three directions between two different GTVs showed no significant difference (P>0.05). There was no difference among any groups in tumor volume (P>0.05). The median DI of GTVPET-reg and GTVPET-ref in GTV3D was 0.82 and 0.86 (P=0.006) The median CI of GTV3D in GTVPET-reg and GTVPET-ref was 0.68 and 0.72 (P=0.006). Conclusions PET/CT can be used to optimize definition of the target volume in EC, but whether the volume or the position, there are no significant difference between the GTVs delineated basing on visual referencing or deformable registration, so, we recommend that radiation oncologists refer to the recent diagnostic PET/CT scan when delineating the GTV for primary thoracic esophageal cancer.